Innovative lamellar crystals-based facial treatment cream with Tubtimsiam pomelo peel extract - keawbankrud, wannisa; Mayomhin, Pichayaporn; Ma-in, Bunthakan (Creative Science, 2024)
This study examined the antioxidant activity of Tabtimsiam pomelo peel extract (Citrus Maxima Burm.f. Merr) and developed facial cream with lamellar crystals. The results of the analysis total phenolic content with Folin-Ciocalteu reagent assay and total flavonoid content with Aluminium chloride colourimetric assay equal to 48.59 ± 0.66 mg GAE g–1 extract and 184.70 ± 7.04 mg QE g–1 extract, respectively. The result of antioxidants activity with DPPH radical scavenging activity reported by IC50 equal to 63.24 ± 16.57 mg mL–1. The development of facial cream with innovative lamellar crystals compared to base cream found that products containing lamellar crystals more stable than base cream and observed by the visual test with a Microscope under Polarized light found that maltiness cross evenly distributed. Finally, the test of facial cream containing Tubtimsiam pomelo peel extract volume 0.1, 0.2 and 0.3% w w–1 compared with base cream after used 4 weeks found that the highest moisturizing was cream containing extract 0.2% w w–1 equal to 247 ± 1.26 μS and glassy skin when visual skin by Dino-Lite camera. GRAPHICAL ABSTRACT HIGHLIGHTS Structure lamellar crystal of facial treatment cream containing Tubtimsiam pomelo peel extract after used 4 weeks found that the highest moisturizing was cream containing extract 0.2% w w–1 equal to 247 ± 1.26 μS and glassy skin